Caracterização in vitro de neuroesferas e seu potencial de regeneração na doença de alzheimer e lesão por stab wound - Paiva, Daisylea de Souza [UNIFESP] (2016)
Objetctive: verify the role of neural stem cells (NSC) in three different aspects: in vitro behaviour, use in memory repair in transgenic animals for Alzheimer's Disease (DA, APPswe/PS1dE9) following transplantation, and expression of proteins related to injury response. Methods: We used in vitro techniques for cell culture of neuroespheres, genome-wide techniques as well as transplantation and behavioral tests. Results: We verified that the APPswe/PS1dE9 transgene affect neurospheres growth rate as well as promoting cellular death. Furthermore, is important to note that differentiated astrocytes from AD animals neurospheres presented hypertrophic morphology, alike the astrocytes from WT animals. Therefore, in this model is possible to identify alterations in NSC as well as soluble amyloid precursor protein secretion during the embrionic stage that can promote proliferation without interfere in the normal development of the animal. When transplanted in transfenic animals for DA, NSCs were able to contribute to neural repair by increasing neurogenesis and secretion of BDNF neurotrophin. Nevertheless there was no effect on memory and habituation in transplanted AD animals. Therefore we demonstrated that even without improving memory at behavioural level, NSC transpantation increased the neurotrophic support in hippocampus and can be responsible for other modifications at molecular level that should be better investigated. From the results of in vitro experiments and to better understand the behaviour of astrocytes in AD we decide to compare the expression pattern of proteins overexpressed at the lesion site of the SW (stab wound). To perform this analysis, we used the genome-wide data from Magdalena Götz's lab to select candidates that could play a role in the stab wound lesion and in AD. Among the top upregulated genes in reactive macroglia (astrocytes and NG2-glia), most of them were related to inflammation and, among these genes we selected four candidates (Osteopontin, CD68 and Galectin-1 and -3). We verified that although they were overexpressed in reactive macroglia after SW injury, the same cells do not express these proteins in AD animals. Whereby SW is an accute injury that is healed within few weeks, we assumed that the downregulation of these proteins could be related to the disease chronicity. Conclusion: By evaluating the in vitro features and role in neurodegeneration processes, we verified that when transplanted, NSC secrete factors that increase the neurotrophic support and during development can play a role in compensating cell death in AD animals. However, in old AD animals macroglial cells do not express proteins that could assist lesion resolution. This work offers insights about the role of NSC and macroglia in Alzheimer's disease.